PENGARUH BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE ANDROID SAMSUNG DI KOTA PALEMBANG - Erresalia Fatriana; Suhartini Karim; Dian Eka (JEMBATAN, 2016)
The purpose of this research is to find variable brand image having influence Purchase Decision of Smartphone Android Samsung in Palembang City both in partial and simultaneous. The theory that is concerned with image was Brand Image, which includes 3 things that are Favorability of Brand Association, Strength of Brand Association, and Uniqueness of Brand Association. Samples taken are 100 people which is users of Smartphone Android Samsung, any kind of type, male and female, aged approximately 17-60 years old, and living in Palembang with data collection method is interview. The instrument of analysis used to answer the purpose research in the top is multiple linear regressions. Simultaneously the result of the research is variable brand image affect on Purchase Decision. Partially, this research result indicates thatStrength of Brand Association is significantly on purchase decision. The findings which were found is that there is no significant influence between Favorability of Brand Association and Uniqueness of Brand Association againts Purchase Decision. Keywords : Brand Image, Favorability of Brand Association, Strength of Brand Association, and Uniqueness of Brand Association, Purchase Decision